Children of Marriages Between Indonesian Citizens and Rohingya: What Are Their Inheritance Rights? - Siti Nur Shoimah; Fahmi Ridlol Uyun (Faculty of Shariah UIN Ponorogo, 2025)
The purpose of this study is to address legal issues related to the rights of children from mixed marriages with stateless persons in Indonesia and to highlight the importance of recognizing children's rights in complex situations involving citizenship status and legal uncertainty. This study employs a normative legal research method by analyzing and examining the regulations governing the status of the Rohingya ethnic group as stateless persons in Indonesia, as well as the inheritance rights of children born to parents who are Indonesian citizens and Rohingya ethnic group members classified as stateless persons. The findings of this study indicate that children born from marriages between Indonesian citizens and stateless Rohingya retain their inheritance rights from both parents. Although such marriages may not be legally registered, they remain valid under religious law, and inheritance rights are based on blood ties, not marriage registration. These children may also inherit land from their Indonesian citizen parents under certain conditions. The contribution of this research lies in its effort to address the gap in legal studies regarding the status of children from mixed marriages with stateless individuals, an issue that has received little attention in national regulations. This study provides an argumentative and normative foundation for the protection of children's rights in transnational and stateless contexts, and encourages the development of more inclusive and equitable legal policies.